Comparison of Shaping Ability of Race and Hero Shaper Instruments in Simulated Curved Canals - Aydin, C.; Inan, U.; Yasar, S.; Bulucu, B.; Tunca, Y.M. (Mosby-Elsevier, 2008)
Objective: This study compared the shaping ability of Hero Shaper and RaCe instruments in simulated curved canals. Study design: Forty simulated canals in resin blocks were divided into 2 experimental groups, each comprising 20 resin blocks, and prepared with Hero Shaper and RaCe using the crown-down technique. Preoperative and postoperative photographs, recorded using a digital camera, were superimposed and aberrations were recorded. Material removal was measured at 10 points beginning 1 mm from the end point of the canal. Mean total widths, outer and inner width measurements, were determined on each central canal path and differences were statistically analyzed using Student t test. Results: The Hero Shaper and RaCe instruments removed almost the same amount of material from the inner side of the simulated canals. On the outer canal wall, the RaCe instruments removed significantly more material from the first 3 mm (P < .05). However, Hero Shaper removed more material from the middle and coronal aspects of the canal and the differences were statistically significant (P < .01). Conclusion: RaCe instruments removed more resin from the outside of the curvature at the apical thirds, while Hero Shaper removed more material from the middle and coronal thirds on the outer canal wall. Hero Shaper instruments showed better centering ability and fewer aberrations. No instrument fractures but some deformations were observed for both systems. © 2008 Mosby, Inc. All rights reserved.